Propolis inhibited Bax expression and increased neuronal count of hippocampal area CA1 in rats receiving sodium nitrite - Kuswati, Kuswati; Handayani, Ety Sari; Nugraha, Zainuri Sabta; Rahmanti, Fishella Aprista; Wicaksana, Zulfikar Loka; Zhafirrahman, Muhammad (Universa Medicina, 2019)
BackgroundSodium nitrite induces hypoxia and oxidative stress in the hippocampus, decreasing the number of neurons in the hippocampus and cognitive function. Propolis contains chrysin that has antioxidant effects that are expected to inhibit neuronal damage in the hippocampus. This study aims to determine the effects of propolis on the expression Bcl-2-associated X protein (Bax) and the number of neurons in the rat hippocampus receiving sodium nitrite.MethodsThis study of laboratory experimental design was conducted on 18 male Wistar strain rats (Rattus norvegicus), they were randomized into 3 groups: one control group (K) received sodium nitrite and two intervention groupsÂ  (P1 and P2) received sodium nitrite and propolis at doses of 100 and 200 mg/kgBW. Treatment with sodium nitrite and propolis were given for 60 days, followed by termination. The number of neurons and Bax expression in the hippocampal CA1 area were measured. One-way ANOVA was used to analyze the data.ResultsThere were significant differences in Bax expression between group K and groups P1 and P2 (p<0.001). The lowest number of neurons in the hippocampal CA1 area was in the K group. There were significant differences in the number of neurons between control (K) group and groups P1 and P2 (p<0.001).ConclusionPropolis inhibited the expression of Bax and decreased the number of neurons in the hippocampal CA1 area of rats receiving sodium nitrite. This study provides information about the benefits of propolis as an antioxidant in the brain.